2020
DOI: 10.1001/jamapsychiatry.2019.3750
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patient Treatment Preference With Dropout and Clinical Outcomes in Adult Psychosocial Mental Health Interventions

Abstract: IMPORTANCEReceiving a preferred treatment has previously been associated with lower dropout rates and better clinical outcomes, but this scenario has not been investigated specifically for psychosocial interventions for patients with a mental health diagnosis.OBJECTIVE To assess the association of patient treatment preference with dropout and clinical outcomes in adult psychosocial mental health interventions via a systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 73 publications
7
70
3
3
Order By: Relevance
“…The increase of therapeutic strategies for depression is of particular importance as it allows better personalization to be provided according to patients’ preferences. In fact, studies have shown that receiving a preferred treatment is associated with stronger therapeutic alliance, lower dropout rates, and positive treatment outcomes (Lindhiem, Bennett, Trentacosta, & McLear, 2014 ; Swift, Callahan, Cooper, & Parkin, 2018 ; Windle et al, 2020 ). It is also essential to routinely evaluate the presence of adverse childhood experiences and traumatic events in people with depression in order to identify if trauma-focused psychotherapies such as EMDR could be more effective for patients with a history of maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of therapeutic strategies for depression is of particular importance as it allows better personalization to be provided according to patients’ preferences. In fact, studies have shown that receiving a preferred treatment is associated with stronger therapeutic alliance, lower dropout rates, and positive treatment outcomes (Lindhiem, Bennett, Trentacosta, & McLear, 2014 ; Swift, Callahan, Cooper, & Parkin, 2018 ; Windle et al, 2020 ). It is also essential to routinely evaluate the presence of adverse childhood experiences and traumatic events in people with depression in order to identify if trauma-focused psychotherapies such as EMDR could be more effective for patients with a history of maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Common sense would suggest that if an individual has a preference for a psychological treatment, they may be more likely to complete it and benefit from it, relative to a treatment they do not prefer. A recent meta-analytic review (Windle et al, 2020) of 29 randomized and non-randomized studies involving 5,294 patients provided evidence to suggest that receiving a preferred psychosocial treatment was associated with lower likelihood of dropping out of treatment (risk ratio (RR)=0.62, 95% confidence interval (CI)=0.48 -0.80). However, receiving one's preferred treatment was not associated with improvement in depression or anxiety (d =0.01,.…”
Section: Preference For Treatmentmentioning
confidence: 99%
“…Although there is evidence that SDM improves patient knowledge about treatment options and increases their sense of involvement in their health care, the effects of SDM on health outcomes at the symptom/syndrome level remain unclear [1]. Across studies where patients with psychiatric disorders are offered a choice between 2 or more treatments, meta-analyses have found that a majority express a preference for psychotherapy over pharmacotherapy, with those receiving their preferred treatment being less likely to drop out, reporting higher treatment satisfaction, and experiencing marginally better clinical outcomes [2-4]. Of note, the majority of studies included in these meta-analyses compared pharmacotherapy to psychotherapy for depression, and the conclusions that could be drawn were significantly limited by heterogeneity across the included studies [5].…”
Section: Introductionmentioning
confidence: 99%